For love of the game - Bernstein, Armyan; Robinson, Amy; Raimi, Sam (USA : Universial Pictures [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor], 1999)
Legendary Detroit Tigers pitcher Bill Chapel has always been better at baseball than at love. Just ask Jane, his on-again, off-again girlfriend. At the end of a dissappointing season, just before what may be the last professional game of his life, Jane tells Billy she's leaving him
Executive ptoducer, Ron Bozman, Mac Abraham, editor, Eric L. Beason, Arthur Coburn
Cast: Kevin Costner, Kelly Preston, John C. Reilly, Jena Malone, Brian Cox
Keywords: Love in motion pictures